Device entrapment during percutaneous coronary intervention. Issue 6 (21st March 2022) - Sanz‐Sánchez, Jorge; Mashayekhi, Kambis; Agostoni, Pierfrancesco; Egred, Mohaned; Avran, Alexandre; Kalyanasundaram, Arun; Garbo, Roberto; Colombo, Antonio; Regazzoli, Damiano; Reimers, Bernhard; Brilakis, Emmanouil S.; Gasparini, Gabriele L.
Abstract: Introduction: Device entrapment is a life‐threatening complication during percutaneous coronary intervention (PCI). However, the success for its management is predominantly based on operator experience with limited available guidance in the published literature. Methods: A systematic review was performed on December 2021; we searched PubMed for articles on device entrapment during PCI. In addition, backward snowballing (i.e., review of references from identified articles and pertinent reviews) was employed. Results: A total of 4209 articles were retrieved, of which 150 studies were included in the synthesis of the data. A methodical algorithmic approach to prevention and management of device entrapment can help to optimize outcomes. The recommended sequence of steps are as follows: (a) pulling, (b) trapping, (c) snaring, (d) plaque modification, (e) telescoping, and (f) surgery. Conclusions: In‐depth knowledge of the techniques and necessary tools can help optimize the likelihood of successful equipment retrieval and minimization of complications.